Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/pai.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of TROP2 Expression in Papillary Thyroid Carcinoma

Abstract: Papillary thyroid carcinoma (PTC) represents the most common primary malignant thyroid lesion in all age groups. As diagnosis of PTC could be challenging in some cases and borderline nuclear features could be seen in some benign mimickers, several immunohistochemical markers are proposed to be helpful for making the correct diagnosis. In this study the authors investigated the diagnostic value of transmembrane glycoprotein (TROP2) for differentiating PTC from other thyroid follicular lesions. A total of 155 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
3
2
0
Order By: Relevance
“…Our study showed positive membranous TROP-2 expression in 97.1% of PTC cases (34 out of 35). These results were consistent with the research conducted by Yang et al [ 1 ], Zargari et al [ 21 ], and Saffer et al [ 23 ]. TROP-2 positivity was 96%, 93%, and 98% in them, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed positive membranous TROP-2 expression in 97.1% of PTC cases (34 out of 35). These results were consistent with the research conducted by Yang et al [ 1 ], Zargari et al [ 21 ], and Saffer et al [ 23 ]. TROP-2 positivity was 96%, 93%, and 98% in them, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed that there is a significant difference in TROP-2 positive expression between PTC cases and non-PTC cases. This result is compatible with Abdou et al [ 3 ], Addati et al [ 22 ], Saffer et al [ 23 ], Bychkov et al [ 8 ], and Lui et al [ 7 ] that reported that TROP-2 is a new marker in the diagnosis of PTC.…”
Section: Discussionsupporting
confidence: 91%
“…In this study the immunohistochemical method was used to assess the TROP2 expression in PTC patients compares with healthy persons . The study results demonstrate that a significant value in TROP2 expression in PTC patients between PTC and control groups , that agree with SAFFAR ,et al 2021 (5) . The present study found that increase TROP2 expression in PTC group.…”
Section: Discussionsupporting
confidence: 90%
“…Trop2 is a transmembrane glycoprotein that is widely expressed on the surface of a variety of epithelial cell carcinoma cells and rarely expressed or not expressed in normal human tissues [24][25][26]. Our previous research found that Trop2 induced epithelial-mesenchymal transition through mediated β-catenin in gastric cancer [18].…”
Section: Discussionmentioning
confidence: 99%